ANALISIS PROFESIONALISME GURU DALAM KONTEKS MENGAJAR DI KELAS MADRASAH ALIYAH DARUL HUDA MANDALAWANGI PANDEGLANG - Fadilah, Fadilah; Nurhakim, M. Syara; Inayatulloh, Siti; Budi, Asep (Staisman Press, 2023)
This research was carried out during the Field Experience Practice (PPL) activities of the Syekh Manshur Islamic College for the 2023 Academic Year. Starting from July 25 to August 24 2023 at MA Darul Huda, Mandalawangi Center. This research uses descriptive qualitative research methods, with data collection tools in the form of observation, documentation and interviews. This research aims to analyze teachers' professional abilities in the context of teaching in the classroom, including mastery of material, structure, concepts and scientific thinking patterns, mastery of competency standards and basic competencies, as well as creative development of material. The method used is a qualitative approach with a descriptive approach. The research results show that teachers' professional abilities in teaching sociology are not yet ideal. It can be seen from the three aspects of teacher assessment that only one aspect is met, namely material mastery ability, structural ability, conceptual ability and scientific thinking ability. Teachers' ability to master competency standards and basic competencies is not yet optimal. The teacher assesses whether students must master basic competency and ability standards, including cognitive, psychomotor or affective abilities, which have been implemented, but the teacher has not implemented them in the classroom teaching process. The teacher's ability to develop material creatively and innovatively has been implemented but is not yet optimal. This can be seen from the minimal use of teaching methods, learning resources and learning media.